2014
DOI: 10.3945/jn.113.178533
|View full text |Cite
|
Sign up to set email alerts
|

Interacting Inflammatory and Growth Factor Signals Underlie the Obesity-Cancer Link

Abstract: The prevalence of obesity, an established risk factor for many chronic diseases (including diabetes, cardiovascular disease, stroke, and several types of cancer), has risen steadily for the past several decades in the United States and many parts of the world. Today, ∼70% of U.S. adults and 30% of children are at an unhealthy weight. The evidence on key biologic mechanisms underlying the obesity-cancer link, with an emphasis on local and systemic inflammatory processes and their crosstalk with energy-sensing g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 39 publications
1
37
0
2
Order By: Relevance
“…Obesity-associated dysfunctional adipose tissue is the "source" of proinflammatory factors, excessive sex steroids and adipokines, which makes adipose tissue a fundamental factor driving the obesity-breast cancer link. The possible mechanisms and factors contributing to the associations between obesity and breast cancer have been reported in previous studies: dysregulation of growth signals, inflammation, bioavailability of sex steroid hormones, microenvironment and metabolic changes in the obese state can all enhance cancer risk and progression (reviewed in (6,7)). …”
Section: Breast Cancer and Obesity Linkmentioning
confidence: 96%
“…Obesity-associated dysfunctional adipose tissue is the "source" of proinflammatory factors, excessive sex steroids and adipokines, which makes adipose tissue a fundamental factor driving the obesity-breast cancer link. The possible mechanisms and factors contributing to the associations between obesity and breast cancer have been reported in previous studies: dysregulation of growth signals, inflammation, bioavailability of sex steroid hormones, microenvironment and metabolic changes in the obese state can all enhance cancer risk and progression (reviewed in (6,7)). …”
Section: Breast Cancer and Obesity Linkmentioning
confidence: 96%
“…Another study showed that IL-6 in periprostatic adipose tissue conditioned medium was approximately 375 times greater than that in patient-matched serum, suggesting that periprostatic adipose tissue may have a role in modulating prostate cancer aggressiveness by serving as a source of IL-6 [115]. The roles of adipose tissue immunity on cancer growth have been discussed in reviews [116,117]. Interestingly, secretion of TNFα and IL-6 contributes to insulin resistance [18] which may subsequently drive the cancer growth when the circulating insulin level is further increased.…”
Section: Cancer Effect Of Cancer Cells On Adipocytes Referencementioning
confidence: 97%
“…The production of pro-inflammatory cytokines (e.g., tumor necrosis factor-alpha, interleukin-6) is triggered by adipose tissue and stimulates the hepatic secretion of acute phase proteins, such as C-reactive protein (CRP) [51] . Thus, greater body fatness is associated with low-grade inflammation both locally, i.e., in adipose tissue, and systemically (reflected by elevated plasma concentrations of inflammatory markers) [85] . Higher circulating inflammatory cytokines have been observed when comparing obese with non-obese individuals [86,87] .…”
Section: Chronic Low-grade Inflammationmentioning
confidence: 99%